High-wear-resistance nano-particle composite polyester fiber spinning oil and preparation method thereof
By introducing anti-wear agents such as modified nano-hydroxymagnesium silicate and smoothing agents such as pentaerythritol oleate into the spinning oil agent, the problem that existing spinning oil agents are difficult to meet the high wear resistance and smoothness requirements of nanoparticle composite polyester fibers is solved, and the high wear resistance and smoothness of the spinning oil agent is achieved, ensuring product quality.
Patent Information
- Application Number
- CN202510330268.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
Existing spinning oil agents are difficult to meet the high wear resistance and smoothness requirements of nanoparticle composite polyester fibers, resulting in poor product quality.
A spinning oil agent containing 3~7 wt% antiwear agent is used. The antiwear agent is composed of modified nano-hydroxymagnesium silicate, polyoxypropylene stearic acid ether and polymethylmethacrylate, and a 45~55 wt% smoothing agent is added. The smoothing agent is a mixture of pentaerythritol oleate and trimethylolpropane fatty acid ester.
It significantly improves the oil film strength and smoothness of the spinning oil agent, meets the spinning requirements of nanoparticle composite polyester fibers, and ensures high quality of the product.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of spinning oils, and specifically relates to a highly wear-resistant nano-particle composite polyester fiber spinning oil and a preparation method thereof. Background Art
[0002] Against the background of rapid development of science and technology, nanoparticle composite polyester fiber, as a new type of fiber with unique properties and versatility, plays an extremely important role in the field of materials science. Nanoparticle composite polyester fiber enhances fiber properties by adding different types of nanoparticles. However, the addition of nanoparticles may cause irregular protrusions, particle aggregation or other defects on the surface of composite polyester fibers due to various factors such as poor dispersibility, irregular particle morphology, and changes in surface energy during processing. These factors work together to increase the surface roughness of nano-composite polyester fibers, thereby increasing the static electricity generated by friction during the spinning process, affecting the smoothness of spinning. Nanoparticle composite polyester fibers pose greater challenges to the smoothness and wear resistance of spinning oils. The wear resistance and smoothness of existing spinning oils cannot meet the spinning requirements of nanoparticle composite fibers, resulting in poor product quality of nanoparticle composite polyester fibers.
[0003] The literature "Research on the Performance and Application of FM-115 Special Oil for Glossy Shaped Polyester FDY" Synthetic Fiber Industry, 2024, 47(03): 42-46.) reported the special oils FM-115 and F1724 for glossy shaped polyester FDY, and compared the performance of the two oils. The oil film strengths of FM-115 and F1724 were 74kg and 63kg respectively; the glossy triangle polyester FDY fiber with a fiber specification of 80dtex / 36f was prepared by using the oil. , , The values are 0.0311, 0.5721 and 0.4050 respectively. The document uses mineral oil and fatty acid ester as lubricants, which results in low oil film strength and poor wear resistance.
[0004] Patent CN118461184A discloses a masterbatch of an anti-wicking DTY oil, an oil and a preparation method thereof, wherein a mixture of propylene glycol methyl ether acetate and tall oil alkyd resin in a ratio of 1:2-4 is selected as a film-forming aid to accelerate the formation speed of the oil film on the fiber surface, improve the oil film strength and fiber smoothness, and the friction coefficient of the fiber obtained by using the oil is about 0.427~0.437. However, propylene glycol methyl ether acetate and tall oil alkyd resin will produce a large amount of volatile organic compounds (VOCs) during use, which will cause potential harm to the environment and health, and is not in line with the concept of green environmental protection development.
[0005] In summary, the wear resistance and smoothness of the high wear-resistant nanoparticle composite polyester fiber spinning oil currently on the market are difficult to meet the spinning requirements of nanoparticle composite polyester fibers. Summary of the invention
[0006] The purpose of the present invention is to provide a highly wear-resistant nanoparticle composite polyester fiber spinning oil and a preparation method thereof, which has excellent wear resistance and smoothness, better meets the spinning requirements of nanoparticle composite polyester fibers, and the oil component is environmentally friendly and easy to prepare.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A highly wear-resistant nano-particle composite polyester fiber spinning oil contains 3-7wt% of an anti-wear agent; the anti-wear agent is composed of a compound of modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate, wherein the mass ratio of the modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate is 1.5:2-3:1-2.
[0008] In some embodiments, the preparation method of modified nano-hydroxy magnesium silicate is as follows: S1. Preparation of Nano-Hydroxy Magnesium Silicate First, 3-5 parts, 5-7 parts and 3-5 parts of sodium hydroxide, magnesium chloride and sodium silicate are weighed and dissolved in 1-3 parts of distilled water respectively; then, the solution is placed in a reaction kettle and reacted at a temperature of 200-250° C. for 6-8 hours; finally, after the reaction is completed, the solution in the reaction kettle is filtered, washed, dried and ground to obtain nano-hydroxy magnesium silicate powder; S2. Modification of Nano-Hydroxy Magnesium Silicate First, weigh 4-6 parts of nano-hydroxy magnesium silicate powder and dissolve it in 2-3 parts of trimethylchlorosilane, and stir it at a speed of 1500-1700 r / min for 40-60 minutes to make the solution fully react; then, add 1-3 parts of sorbitan stearate and / or polyoxyethylene sorbitan monostearate to the reaction solution and continue to react for 20-40 minutes; finally, cool it to room temperature to obtain modified nano-hydroxy magnesium silicate.
[0009] Nano-hydroxy magnesium silicate itself is an excellent anti-wear agent. Its anti-friction and anti-wear properties are achieved through physical effects such as adsorption, spreading, and filling on the rough fiber surface and friction chemical reactions on the rough fiber surface. The modified nano-hydroxy magnesium silicate can be better compatible with other ingredients in the oil formulation, thereby improving the overall wear resistance of the oil. Stearic acid polyoxypropylene ether can be used as an oil film enhancer. Stearic acid polyoxypropylene ether belongs to the polyether class and is composed of long-chain molecules with very strong polarity. It can form an adsorption layer on the fiber surface. Adding it to the oil can enhance the oil film strength. Polymethyl methacrylate is a high molecular polymer with a chain structure. It can change the overall viscosity of the oil by changing its proportion in the oil, thereby achieving the purpose of changing the oil film strength of the oil. After the three are mixed, polymethyl methacrylate can promote the oil film enhancement effect of stearic acid polyoxypropylene ether, and the three have a synergistic effect, which greatly improves the oil film strength of the oil.
[0010] Furthermore, the highly wear-resistant nanoparticle composite polyester fiber spinning oil contains 45-55wt% of a smoothing agent, and the smoothing agent is a compound of pentaerythritol oleate and trimethylolpropane fatty acid ester, specifically a 1-1.5:1-2 ratio of pentaerythritol oleate and trimethylolpropane fatty acid ester.
[0011] Pentaerythritol oleate is a lubricant with excellent performance. Its molecule contains a long oleic acid chain. These long-chain fatty acid groups can combine with each other through intermolecular forces such as van der Waals force or hydrogen bond to form a stable structure, which makes it have good lubrication properties. It can form a protective film on the fiber surface, which can effectively reduce friction on the fiber surface and provide good smoothness. In addition, the oleic acid group in the molecule can effectively interact with other fat-soluble substances in the oil, and the hydrophilic part of pentaerythritol helps it to be compatible with the aqueous substances in the oil. This balance of lipophilicity and hydrophilicity makes pentaerythritol oleate have good dispersibility and lubricity in spinning oil, further enhancing its smoothing effect.
[0012] Trimethylolpropane fatty acid ester has excellent chemical stability. It can form a uniform film on the fiber surface, making the fiber surface smoother, reducing the fiber surface roughness and the friction between fibers and between fibers and spinning components. In addition, trimethylolpropane fatty acid ester has low volatility and can better avoid problems such as wear of fibers due to oil volatilization in high temperature environments. The combined effect of pentaerythritol oleate and trimethylolpropane fatty acid ester can effectively reduce the fiber surface roughness, reduce the friction between fibers and between fibers and spinning components, make spinning go smoothly, and ensure product quality.
[0013] Since the surface roughness of nanoparticle composite polyester fiber is large, higher requirements are put forward for the smoothness and wear resistance of spinning oil. The present invention introduces anti-wear agent into spinning oil and studies the relationship between the structure and performance of smoothing agent in oil to enhance the oil film strength and smoothness of nanoparticle composite polyester fiber spinning oil.
[0014] As the preferred technical solution: The highly wear-resistant nanoparticle composite polyester fiber spinning oil as described above further contains 15-25wt% of an emulsifier, and the emulsifier is one or a combination of isotridecanol polyoxyethylene ether and sorbitan fatty acid ester.
[0015] The highly wear-resistant nanoparticle composite polyester fiber spinning oil as described above also contains 3-6wt% of a penetrant, and the penetrant is fatty alcohol polyoxyethylene ether JFC.
[0016] The highly wear-resistant nanoparticle composite polyester fiber spinning oil as described above also contains 2-5wt% of a sizing agent, which is one or a combination of coconut oil diethanolamide and oleic acid triethanolamine salt.
[0017] The highly wear-resistant nanoparticle composite polyester fiber spinning oil as described above also contains 15-20wt% of an antistatic agent, and the antistatic agent is a potassium salt of fatty alcohol phosphate polyoxyethylene ether.
[0018] The highly wear-resistant nanoparticle composite polyester fiber spinning oil as described above also contains 1-3wt% of an anti-coking agent, which is a double-terminated surfactant of fatty acid methyl ester ethoxylate.
[0019] The highly wear-resistant nanoparticle composite polyester fiber spinning oil as described above has a spinning speed of 3700 m / min, a stretching temperature of 90° C., and a setting temperature of 170° C. during the spinning process.
[0020] The present invention also provides a method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil as described in any one of the above items, comprising the following steps: S1. Weigh and prepare the materials required according to actual use requirements; S2. Add lubricant, emulsifier, penetrant, clustering agent, antistatic agent, antiwear agent and anti-coking agent in sequence to mix all materials evenly; S3. Control the temperature of the reactor at 40°C-50°C, set the stirring speed at 500-900 r / min, and react for 1.5-3 hours to obtain a highly wear-resistant nanoparticle composite polyester fiber spinning oil.
[0021] Beneficial effects: (1) The highly wear-resistant nanoparticle composite polyester fiber spinning oil of the present invention has high wear resistance and smoothness, and can better meet the spinning requirements of nanoparticle composite polyester fibers.
[0022] (2) The oil of the present invention contains an anti-wear agent, which is a mixture of modified nano-hydroxy magnesium silicate, polyoxypropylene stearate ether and polymethyl methacrylate. The three agents act synergistically and promote each other, thereby greatly improving the oil film strength of the oil, effectively improving the wear resistance of the oil, and ensuring product quality.
[0023] (3) The oil agent of the present invention uses a mixture of pentaerythritol oleate and trimethylolpropane fatty acid ester as a lubricant. The combined effect of pentaerythritol oleate and trimethylolpropane fatty acid ester can quickly form a uniform oil film on the fiber surface, enhance the smoothness of the fiber, thereby effectively reducing the roughness of the fiber surface, reducing the friction between fibers and between fibers and spinning components, allowing spinning to proceed smoothly and ensuring product quality.
[0024] (4) The oil of the present invention enhances the oil film strength and smoothness of the nanoparticle composite polyester fiber spinning oil by introducing an anti-wear agent into the oil and studying the relationship between the structure and performance of the smoothing agent in the oil. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0026] Conductivity (10% aqueous solution): Water was added to the oil prepared in the following examples, with the water accounting for 10% of the total solution, measured according to GB / T11007; Oil film strength: Use a four-ball friction tester to measure the oil film strength of the sample to be tested in accordance with GB / T 3142-1982 "Determination of Lubricant Load-bearing Capacity (Four-ball Method)"; Surface tension (1% aqueous solution): measured at 25°C using a QBZY platinum plate surface tension meter (QBZY-1, Shanghai Fangrui Instrument Co., Ltd.); Fiber specific resistance: measured using an automatic digital fiber specific resistance meter in accordance with GB / T14342-2015; Fiber friction coefficient: measured by LFY-110 yarn dynamic friction tester (LFY-110, Shandong Textile Science Research Institute); Oil content: The oil content was determined using a fiber grease quick extractor (Model YG981, Changzhou Shuanggu Dunda Electromechanical Technology Co., Ltd.) in accordance with the national standard GB / T6504-2008.
[0027] The following are the manufacturers and brands of the raw materials involved in the embodiments: Sodium hydroxide: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number 1310-73-2; Magnesium chloride: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 7786-30-3; Sodium silicate: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 1344-09-8; Trimethylchlorosilane: The manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 75-77-4; Sorbitan stearate: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 1338-41-6; Polyoxyethylene sorbitan monostearate: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 1338-41-6; Stearic acid polyoxypropylene ether: the manufacturer is Merck Group, Darmstadt, Germany, the brand number is 25231-21-4; Polymethyl methacrylate: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 9011-14-7; Pentaerythritol oleate: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 19321-40-5; Trimethylolpropane fatty acid ester: the manufacturer is Shanghai Yucheng Chemical Co., Ltd.; Isotridecyl polyoxyethylene ether: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 61827-42-7; Sorbitan fatty acid ester: The manufacturer is Nantong Ningyuan New Material Technology Co., Ltd. Fatty alcohol polyoxyethylene ether JFC: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 68131-39-5; Coconut oil diethanolamide: The manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., the brand number is 6863-42-9; Oleic acid triethanolamine salt: the manufacturer is Shanghai McLean Biochemical Technology Co., Ltd., the brand number is 2717-15-9; Fatty alcohol phosphate polyoxyethylene ether potassium salt: manufacturer is Huayuan.com, brand number is 39322-78-6; Fatty acid methyl ester ethoxylate type double-end-capped surfactant: manufacturer is Aladdin Reagent (Shanghai) Co., Ltd., brand number is 65218-33-7; Example 1: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil, the specific steps are as follows: (1) Preparation of raw materials; Antiwear agent: modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether, polymethyl methacrylate; Smoothing agent: pentaerythritol oleate, trimethylolpropane fatty acid ester; Emulsifier: isotridecanol polyoxyethylene ether; Penetrant: fatty alcohol polyoxyethylene ether JFC; Binder: Coconut oil diethanolamide; Antistatic agent: fatty alcohol phosphate polyoxyethylene ether potassium salt; Anti-coking agent: fatty acid methyl ester ethoxylate type double-terminated surfactant.
[0028] (2) Anti-wear agent configuration: The modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate are prepared in a mass ratio of 1.5:2.5:1.5 to obtain an anti-wear agent; (3) Preparation of smoothing agent: Pentaerythritol oleate and trimethylolpropane fatty acid ester are prepared in a mass ratio of 1:1.5 to obtain a smoothing agent; (4) Weigh 4 wt% of an anti-wear agent, 50 wt% of a smoothing agent, 20 wt% of an emulsifier, 4 wt% of a penetrant, 4 wt% of a sizing agent, 16 wt% of an antistatic agent, and 2 wt% of an anti-coking agent in proportion, and then add the smoothing agent, emulsifier, penetrant, sizing agent, antistatic agent, anti-wear agent, and anti-coking agent in sequence; then react at a temperature of 45 ° C and a stirring speed of 700 r / min for 2 h to obtain a highly wear-resistant nanoparticle composite polyester fiber spinning oil.
[0029] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1096 μS / cm, an oil film strength of 1048.6 N, and a surface tension of 33.54 mN / m.
[0030] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 5.4×10 7 Ω.cm, the fiber friction coefficient is 0.3359, and the oil content is 0.81%.
[0031] Comparative Example 1: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil is basically the same as Example 1, except that the anti-wear agent is composed only of modified nano-hydroxy magnesium silicate.
[0032] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1025 μS / cm, an oil film strength of 980 N, and a surface tension of 32.89 mN / m.
[0033] The final nanoparticle composite polyester fiber has a fiber specification of 81dtex / 48f and a fiber specific resistance of 6.3×10 7 Ω.cm, the fiber friction coefficient is 0.3275, and the oil content is 0.72%.
[0034] Comparative Example 2: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil is basically the same as Example 1, except that the anti-wear agent is composed only of stearic acid polyoxypropylene ether.
[0035] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1039 μS / cm, an oil film strength of 980 N, and a surface tension of 34.27 mN / m.
[0036] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 6.1×10 7 Ω.cm, the fiber friction coefficient is 0.3521, and the oil content is 0.88%.
[0037] Comparative Example 3: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil is basically the same as Example 1, except that the anti-wear agent is composed only of polymethyl methacrylate.
[0038] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1041 μS / cm, an oil film strength of 1048.6 N, and a surface tension of 33.36 mN / m.
[0039] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 5.9×10 7 Ω.cm, the fiber friction coefficient is 0.3887, and the oil content is 0.79%.
[0040] Comparative Example 4: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil is basically the same as Example 1, except that the smoothing agent is composed only of pentaerythritol oleate.
[0041] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 981 μS / cm, an oil film strength of 980 N, and a surface tension of 33.89 mN / m.
[0042] The final nanoparticle composite polyester fiber has a fiber specification of 79dtex / 48f and a fiber specific resistance of 9.1×10 7 Ω.cm, the fiber friction coefficient is 0.3961, and the oil content is 0.71%.
[0043] Comparative Example 5: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil is basically the same as Example 1, except that the smoothing agent is composed only of trimethylolpropane fatty acid ester.
[0044] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1005 μS / cm, an oil film strength of 1048.6 N, and a surface tension of 33.36 mN / m.
[0045] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 8.2×10 7 Ω.cm, the fiber friction coefficient is 0.36912, and the oil content is 0.80%.
[0046] Example 2: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil, the specific steps are as follows: (1) Preparation of raw materials; Antiwear agent: modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether, polymethyl methacrylate; Smoothing agent: pentaerythritol oleate, trimethylolpropane fatty acid ester; Emulsifier: isotridecanol polyoxyethylene ether; Penetrant: fatty alcohol polyoxyethylene ether JFC; Binder: Coconut oil diethanolamide; Antistatic agent: fatty alcohol phosphate polyoxyethylene ether potassium salt; Anti-coking agent: fatty acid methyl ester ethoxylate type double-terminated surfactant.
[0047] (2) Anti-wear agent configuration: The modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate are prepared in a mass ratio of 1.5:2:1 to obtain an anti-wear agent; (3) Preparation of smoothing agent: Pentaerythritol oleate and trimethylolpropane fatty acid ester are prepared in a mass ratio of 1.25:1 to obtain a smoothing agent; (4) Weigh 3 wt% of anti-wear agent, 45 wt% of smoothing agent, 25 wt% of emulsifier, 6 wt% of penetrant, 5 wt% of agglomerating agent, 15 wt% of antistatic agent and 1 wt% of anti-coking agent in proportion, then add the smoothing agent, emulsifier, penetrant, agglomerating agent, antistatic agent, anti-wear agent and anti-coking agent in sequence; then react at a temperature of 40 ° C and a stirring speed of 500 r / min for 1.5 h to obtain a highly wear-resistant nanoparticle composite polyester fiber spinning oil.
[0048] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 999 μS / cm, an oil film strength of 980 N, and a surface tension of 33.41 mN / m.
[0049] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 8.9×10 7 Ω.cm, the fiber friction coefficient is 0.3297, and the oil content is 0.79%.
[0050] Example 3: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil, the specific steps are as follows: (1) Preparation of raw materials; Antiwear agent: modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether, polymethyl methacrylate; Smoothing agent: pentaerythritol oleate, trimethylolpropane fatty acid ester; Emulsifier: sorbitan fatty acid ester; Penetrant: fatty alcohol polyoxyethylene ether JFC; Bunching agent: triethanolamine oleate; Antistatic agent: fatty alcohol phosphate polyoxyethylene ether potassium salt; Anti-coking agent: fatty acid methyl ester ethoxylate type double-terminated surfactant.
[0051] (2) Anti-wear agent configuration: The modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate are prepared in a mass ratio of 1.5:2.25:2 to obtain an anti-wear agent; (3) Preparation of smoothing agent: Pentaerythritol oleate and trimethylolpropane fatty acid ester are prepared in a mass ratio of 1.5:2 to obtain a smoothing agent; (4) Weigh 7 wt% of anti-wear agent, 55 wt% of smoothing agent, 15 wt% of emulsifier, 3 wt% of penetrant, 2 wt% of agglomerating agent, 15 wt% of antistatic agent, and 3 wt% of anti-coking agent in proportion, and then add the smoothing agent, emulsifier, penetrant, agglomerating agent, antistatic agent, anti-wear agent, and anti-coking agent in sequence; then react at a temperature of 50 ° C and a stirring speed of 900 r / min for 3 h to obtain a highly wear-resistant nanoparticle composite polyester fiber spinning oil.
[0052] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1095 μS / cm, an oil film strength of 1048.6 N, and a surface tension of 32.79 mN / m.
[0053] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 5.4×10 7 Ω.cm, the fiber friction coefficient is 0.3271, and the oil content is 0.81%.
[0054] Example 4: A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil, the specific steps are as follows: (1) Preparation of raw materials; Antiwear agent: modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether, polymethyl methacrylate; Smoothing agent: pentaerythritol oleate, trimethylolpropane fatty acid ester; Emulsifier: a mixture of isotridecanol polyoxyethylene ether and sorbitan fatty acid ester in a mass ratio of 1:1; Penetrant: fatty alcohol polyoxyethylene ether JFC; Sizing agent: a mixture of coconut oil diethanolamide and oleic acid triethanolamine salt in a mass ratio of 2:1; Antistatic agent: fatty alcohol phosphate polyoxyethylene ether potassium salt; Anti-coking agent: fatty acid methyl ester ethoxylate type double-terminated surfactant.
[0055] (2) Anti-wear agent configuration: The modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate are prepared in a mass ratio of 1.5:1.75:1.75 to obtain an anti-wear agent; (3) Preparation of smoothing agent: Pentaerythritol oleate and trimethylolpropane fatty acid ester are prepared in a mass ratio of 1:1 to obtain a smoothing agent; (4) Weigh 5 wt% of an anti-wear agent, 47 wt% of a smoothing agent, 16 wt% of an emulsifier, 5 wt% of a penetrant, 5 wt% of a sizing agent, 20 wt% of an anti-static agent, and 2 wt% of an anti-coking agent in proportion, and then add the smoothing agent, emulsifier, penetrant, sizing agent, anti-static agent, anti-wear agent, and anti-coking agent in sequence; then react at a temperature of 47 ° C and a stirring speed of 850 r / min for 2.5 h to obtain a highly wear-resistant nanoparticle composite polyester fiber spinning oil.
[0056] The final highly wear-resistant nanoparticle composite polyester fiber spinning oil is colorless and transparent, with an electrical conductivity of 1011 μS / cm, an oil film strength of 1048.6 N, and a surface tension of 33.62 mN / m.
[0057] The final nanoparticle composite polyester fiber has a fiber specification of 80dtex / 48f and a fiber specific resistance of 7.4×10 7 Ω.cm, the fiber friction coefficient is 0.3296, and the oil content is 0.80%.
[0058] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A highly wear-resistant nanoparticle composite polyester fiber spinning oil, characterized in that: Contains 3-7 wt% of an anti-wear agent; the anti-wear agent is composed of a compound of modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate, wherein the mass ratio of modified nano-hydroxy magnesium silicate, stearic acid polyoxypropylene ether and polymethyl methacrylate is 1.5:2-3:1-2.
2. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The preparation method of modified nano hydroxy magnesium silicate is as follows: S1. Preparation of Nano-Hydroxy Magnesium Silicate: First, 3-5 parts, 5-7 parts and 3-5 parts of sodium hydroxide, magnesium chloride and sodium silicate are weighed and dissolved in 1-3 parts of distilled water respectively; then, the solution is placed in a reaction kettle and reacted at a temperature of 200-250° C. for 6-8 hours; finally, after the reaction is completed, the solution in the reaction kettle is filtered, washed, dried and ground to obtain nano-hydroxy magnesium silicate powder; S2. Modification of Nano-Hydroxy Magnesium Silicate: First, weigh 4 to 6 parts of nano-hydroxy magnesium silicate powder and dissolve it in 2 to 3 parts of trimethylchlorosilane, and stir it at a speed of 1500 to 1700 r / min for 40 to 60 minutes to allow the solution to react fully; then, add 1 to 3 parts of sorbitan stearate and / or polyoxyethylene sorbitan monostearate to the reaction solution and continue to react for 20 to 40 minutes; finally, cool it to room temperature to obtain modified nano-hydroxy magnesium silicate.
3. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 2, characterized in that: In the step S1, the mixed solution after the reaction is washed 2-3 times with distilled water; in the step S1, the drying temperature of the filtered product is 80-120°C.
4. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The highly wear-resistant nanoparticle composite polyester fiber spinning oil also contains 45-55wt% of a smoothing agent, which is a compound of pentaerythritol oleate and trimethylolpropane fatty acid ester, wherein the mass ratio of pentaerythritol oleate to trimethylolpropane fatty acid ester is 1-1.5:1-2.
5. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The highly wear-resistant nano-particle composite polyester fiber spinning oil further contains 15-25wt% of an emulsifier, and the emulsifier is one or a combination of isotridecanol polyoxyethylene ether and sorbitan fatty acid ester.
6. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The spinning oil for highly wear-resistant nano-particle composite polyester fibers also contains 3-6 wt % of a penetrant, and the penetrant is fatty alcohol polyoxyethylene ether JFC.
7. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The high wear-resistant nano-particle composite polyester fiber spinning oil also contains 2-5wt% of a sizing agent, which is one or a combination of coconut oil diethanolamide and oleic acid triethanolamine salt.
8. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The oil also contains 15-20wt% of an antistatic agent, which is a potassium salt of fatty alcohol phosphate polyoxyethylene ether.
9. The highly wear-resistant nanoparticle composite polyester fiber spinning oil according to claim 1, characterized in that: The oil agent also contains 15-20wt% of an anti-coking agent, which is a double-terminated surfactant of fatty acid methyl ester ethoxylate type.
10. A method for preparing a highly wear-resistant nanoparticle composite polyester fiber spinning oil, comprising preparing the highly wear-resistant nanoparticle composite polyester fiber spinning oil as claimed in any one of claims 1 to 9, characterized in that: S1. Weigh and prepare the materials required according to actual use requirements; S2, add lubricant, emulsifier, penetrant, clustering agent, antistatic agent, antiwear agent, anti-coking agent to the reactor in sequence to mix all the materials thoroughly and evenly; S3. Control the temperature of the reactor at 40°C~50°C, set the stirring speed at 500~900r / min, and react for 1.5~3h.
Citation Information
Patent Citations
Oil agent for improving friction coefficient stability of automotive upholstery fabric
CN106400482A
Special polyester high-speed spinning oiling agent capable of being directly oiled by crude oil and preparation method of special polyester high-speed spinning oiling agent
CN117127287A
Stock solution oiling type para-aramid spinning oil
CN117587626A
Self-emulsifying low-smoke ester, preparation method thereof and spinning oil composition
CN117776992A
Resin composition containing oil
JP1982195152A
Cited By
Oiling agent for preparing liquid crystal polyarylester fiber and preparation method and application of liquid crystal polyarylester fiber
CN120649198A
Diesel oil anti-wear agent and preparation process thereof
CN121538004A